Building a Community of Designers: Restructuring Learning Through Student Hypermedia Design - Julie Erickson (Journal of Research in Rural Education, 1997)
How do we create better learning environments in the classroom? Some researchers advocate restructuring the classroom through student design-based inquiry. This paper reports a year-long classroom study that used student design-based inquiry to reform the classroom toward more constructivist teaching and learning practices. Two teachers in a rural school and their 125 seventh graders attempted to build a classroom community of designers, where students learned a variety ofresearch and communication skills through designing hypermedia documents. Results ofinitial qualitative analyses show the development of the classroom over the school year (including the new roles for teachers and students) and challenges from the institution ofschooling. The paperfocuses on the perspective ofone ofthe participating teachers in the study, using data primarily from his journals to illustrate the evolution of instructional practices and student learning throughout the year.